Speculation and its effects - Moore, Harry Elbridge (My University, 1891)
Introduction: In general speculation is the buying or selling of any commodity whatsoever with the idea of gaining by the rise or fall of price, and without the intent or expectation of supplying any want in the community. The commonly accepted sense in which we use the word, however, and the one in which I wish to speak of it is as applied to gambling in the commercial circles formed for the purpose. Of such circles there are many but as Wall Street is the oldest and most extensive speculative center in the United States I shall speak of it in a general way as typical of them all. The effect which Wall Street has had upon the industries of this county can probably never be satisfactorily determined since it is so intimately connected with all commercial interests. Theoretically Wall Street is a great money market where commodities are dealt in according to their real values—an institution having little or no effect outside of its over limits save to serve as an index to the county’s welfare and prosperity.
Citation: Moore, Harry Elbridge. Speculation and its effects. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Wall Street; Stocks; Trade; Capitalism; Economics; Theses; Manuscripts (documents)